2021
DOI: 10.1016/j.eclinm.2021.100727
|View full text |Cite
|
Sign up to set email alerts
|

A global point prevalence survey of antimicrobial use in neonatal intensive care units: The no-more-antibiotics and resistance (NO-MAS-R) study

Abstract: Background Global assessment of antimicrobial agents prescribed to infants in the neonatal intensive care unit (NICU) may inform antimicrobial stewardship efforts. Methods We conducted a one-day global point prevalence study of all antimicrobials provided to NICU infants. Demographic, clinical, and microbiologic data were obtained including NICU level, census, birth weight, gestational/chronologic age, diagnoses, antimicrobial therapy (reason for use; length of therapy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 67 publications
2
51
1
Order By: Relevance
“…Gentamycin was the most common antibiotic prescribed in our NICU (72.22%), followed by cefotaxime (71.60%). This finding was similar to the results of studies conducted by Prusakov et al [2]. A combination of meropenem and amikacin was the recommended antibiotic therapy in a study by Weldu et al, while in our study the most commonly selected combination antibiotic in the NICU was cefotaxime and gentamycin [18].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Gentamycin was the most common antibiotic prescribed in our NICU (72.22%), followed by cefotaxime (71.60%). This finding was similar to the results of studies conducted by Prusakov et al [2]. A combination of meropenem and amikacin was the recommended antibiotic therapy in a study by Weldu et al, while in our study the most commonly selected combination antibiotic in the NICU was cefotaxime and gentamycin [18].…”
Section: Discussionsupporting
confidence: 92%
“…Sepsis was confirmed in only 16.36% of all cultures included in our study. this rate was higher than the one found by Tank et al, who reported only 4% culture positivity, but it was similar to that reported by Prusakov et al, citing 20% confirmed sepsis cases in their study [2,14]. Low culture positivity is a common problem in pediatric patients, particularly in neonates.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The US component of the bilateral TTT NICU‐ASP provides 2‐weeks of training in a Level IV NICU with an established multidisciplinary NICU‐ASP at NCH 11,12 . Our goal was to teach South African pharmacists the role of a NICU pharmacist to promote the judicious use of antimicrobials and enhance the quality of care of neonates.…”
Section: Methodsmentioning
confidence: 99%